Discovery of reversible selective monoamine oxidase B inhibitors with anti-acetylcholinesterase activity derived from 4-oxo-N-4-diphenyl butanamides - Jana S.; Nasreen T.; Singh S.K. (My University, 2025)
Aim: Multitargeted drugs are essential for the treatment of various neurodegenerative disorders, because of their complex nature. This study aimed to develop novel small molecules as selective monoamine oxidase B (MAO-B) inhibitors with cholinesterase inhibition. Materials & methods: With the help of fragment-based drug design, some 4-oxo-N-4-diphenyl butanamides were designed and synthesized as MAO-B inhibitors with anti-acetylcholinesterase (AChE) activity. Results: Compound 6m showed the best neuroprotection, with reversible selective MAO-B inhibition activity (IC50 = 11.54 ± 0.64 nM). Compounds 6b, 6h, 6j, 6n and 6p (IC50 = 20.90 ± 0.50, 17.25 ± 0.90, 15.85 ± 0.16, 16.81 ± 0.85 and 25.19 ± 0.17 nM, respectively) also appeared as potent and selective MAO-B inhibitors with anti-AChE activity. Conclusion: The present study suggests potent, neuroprotective and nontoxic lead compounds as selective MAO-B inhibitors with anti-AChE activity. © 2023 Newlands Press.